Gross anatomy of the nasal cavity of buffalo calves - Naik, S Ganga; Ananda, K J; Rani, B Kavitha; Khandare, S M (The Indian Journal of Animal Sciences, 2011)
In the present study the local crossbred buffalo calves of approximately 6 to 12 months old were examined to document the gross anatomy of the nasal cavity. The study revealed that the nasal cavity of calves was completely divided into two compartments by a median nasal septum. The dorsal nasal turbinate was the longest and extended from the cribriform plate of ethmoid bone to the level of third tranverse rugae of the hard palate. It continued rostrally as straight fold and contained a sinus. The ventral nasal turbinate was cylindrical in shape and extended from the first molar to the fourth transverse rugae of the hard palate. The middle nasal turbinate/ethmoturbinate was triangular in outline and extended up to the Third premolar tooth. The ethmoidal labyrinth composed of 6 endoturbinates and 8 ectoturbinates.